Influential factors for successful adoption of future school curriculum - Lovemore Motsi; Phumza Makgato-Khunou (AOSIS, 2024)
Background: Implementing curriculum reforms can be difficult because they call for several adjustments that may contradict deeply ingrained subjective realities and pre-existing beliefs in both the individual and organisational contexts. Aim: This study was sought to investigate the factors that influence the successful adoption of future school curriculum. Setting: The study was conducted in secondary schools in Tshwane South district. Methods: Six hundred questionnaires were distributed to teachers in 10 secondary schools; 496 of the 600 surveys that were sent out were returned, yielding a 67% response rate. A total of 444 questionnaires were processed for analysis after 52 were discarded because of spoilage. Confirmatory factor analysis (CFA) and structural equation modelling (SEM) were used to analyse quantitative data. Results: School leadership support and teacher professional development have a significant impact on the successful adoption of future school curricula. Conclusion: It is evident that teachers need professional development that is available to them in a range of settings and that includes materials that will facilitate their ability to teach classes. Contribution: This study adds to the body of knowledge by presenting a novel theory, curriculum-based reform (CBR) theory, which developed from the task-technology fit (TTF) theory and looked into what factors influence the successful adoption of future school curricula.